Mission-critical active directory : - Balladelli, Micky (Digital press, 2001)
Mission-Critical Active Directory provides systems designers and administrators within growing and large organizations with techniques and insights into Active Directory. Using this information, they can build a Windows 2000 network that reliably accommodates many thousands of new users, computers, and programs. Few individuals possess the knowledge of Active Directory design, operation, and security necessary to build a truly secure and stable Windows 2000 system